2008
DOI: 10.1111/j.1600-0560.2007.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma with squamous and sarcomatous differentiation

Abstract: Merkel cell carcinoma is an aggressive neuroendocrine tumor historically thought to arise from neural crest-derived cutaneous neuroendocrine cells. Recent evidence supports an epidermal origin. We present a case of Merkel cell carcinoma arising on the upper arm of a 94-year-old woman that had multiple morphologic patterns: small cells typical of Merkel cell carcinoma, malignant cells with squamous differentiation and malignant poorly differentiated spindle cells. Subsequent metastatic disease in regional lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Other skin carcinomas that sometimes feature squamous differentiation include Merkel cell carcinoma (MCC), porocarcinoma, and sebaceous carcinoma [23, 27, 28]. This is likely a manifestation of divergent differentiation of the tumor or varied differentiation of tumor stem cells.…”
Section: Other Malignant Tumors That Mimic Primary Cutaneous Sccmentioning
confidence: 99%
“…Other skin carcinomas that sometimes feature squamous differentiation include Merkel cell carcinoma (MCC), porocarcinoma, and sebaceous carcinoma [23, 27, 28]. This is likely a manifestation of divergent differentiation of the tumor or varied differentiation of tumor stem cells.…”
Section: Other Malignant Tumors That Mimic Primary Cutaneous Sccmentioning
confidence: 99%
“…[3] The neoplastic cells were initially thought to arise from the Merkel cells; however, origin from a stem cell, able to differentiate along different cell lines, is favored. [4] Moreover the tumor has been recognized in many extracutaneous sites like esophagus and salivary glands. [2] Incidence peaks in 7 th to 9 th decades of life; however, younger age group is not exempted.…”
Section: Discussionmentioning
confidence: 99%
“…Sirikanjanapong et al [26] reported a case of intraepidermal and dermal MCC with squamous cell carcinoma in situ. Hwang et al [27] reported a case of MCC with squamous and sarcomatous differentiations. Jones et al [28] reported a case showing a development of cutaneous NEC mixed with squamous cell carcinoma in erythema.…”
Section: Discussionmentioning
confidence: 99%